Legal Education through a Social Justice Lens: A Framework for Teaching Law in the South African Context - Van Heerden, Jennifer (Department of Public Law, 2015)
This research seeks to establish a framework for teaching law that enables graduates to practice law in a manner that furthers social justice. The first half of this paper investigates why it is legitimate to prioritize social justice in the Legal Education discipline. Three sets of literature support this argument. First, South African higher education policy, which emphasizes the need to produce graduates who are able to contribute to societal transformation. Second, the University of Cape Town's Social Responsiveness Policy and the University's Strategies for Change, which mirror national higher education priorities. The third set comprises discussions emerging from Critical Legal Studies as to the purpose of Legal Education. The second half of this paper turns to the framework itself. Experiential learning theory and Paulo Freire's "critical consciousness" shape the design of the three-pillared framework. The three pillars emerging are: social consciousness, sensitivity to context, and critical, social-orientated thinking. This framework embodies the kind of commitment to social justice needed for transformation in South Africa.